Students' Views on Multimedia in Differentiated Learning of Pancasila Education at SMA Muhammadiyah 10 Surabaya - Widyatama, Pandu Rudy; Muhajir, Muhajir; Huda, Nuril (Journal of Educational Sciences, 2025)
The research is based on challenges in learning Pancasila Education which is often considered monotonous and less attractive to students, so innovation in learning methods is needed. This study aims to explore how students assess the effectiveness of the use of multimedia in differentiated-based Pancasila Education learning at SMA Muhammadiyah 10 Surabaya. This study uses a qualitative descriptive approach using a case study method, involving six students, two teachers, and the principal as research subjects. Data was collected through interviews, participatory observations, and documentation, then analyzed using the Miles and Huberman technique. The results of the study show that the integration of multimedia in differentiated learning can realize student involvement in the process of learning Pancasila values. Multimedia such as videos, images, and interactive platforms are effective in accommodating various student learning styles, both visual, auditory, and kinesthetic. However, some technical challenges such as unstable internet connections and projector device issues are still a hindrance. In conclusion, the use of multimedia in differentiated learning has a positive impact, but improvements in technological infrastructure and teacher training are needed to optimize its effectiveness. The suggestion for schools is to work to improve multimedia facilities and ensure adequate tools to support inclusive and effective learning.